Review of Contemporary Literature in English: Selected Historical, Social and Cultural Contexts by Jana Javorčíková (American & British Studies Annual, 2013)
Review of Contemporary Literature in English: Selected Historical, Social and Cultural Contexts by Jana Javorčíková (Banská Bystrica : FHV UMB, 2012. 203 p. ISBN 978-80-557-0430-2)